Modeling and optimization of electro discharge coating parameters for coating of aluminum alloy using WC/Ni electrode. (April 2023) - Srikanth, S.; Senthilkumar, C.; Elaiyarasan, U.
Abstract: Aluminum alloys have acquired a considerable interest in the automotive and aerospace industries as a steel substitute, especially in sliding components because of its light weight. However, its surface properties are inferior. To address this issue, surface modiﬁcation is required for to enhance the wear resistance and reliability. Hence the current study focuses on enhancing the surface properties by coating on the surface of aluminum alloys with a hard partially sintered WC/Ni electrode which is made with the PM route by electro discharge coating (EDC). Experiments are carried out according to central composite design (CCD). Optimal coating parameters were identified by using desirability approach. Corresponding to highest desirability, the optimal combination of discharge parameters are Compaction load = 154.5082Mpa, Current = 7.3842amps and Pulse on time = 20.5282µs and the responses attained are MH = 753.8 HV and SR= 2.948 µm. To observe topographical changes during EDC was carried out through SEM to ascertain the various mechanisms on coated surface and EDS were used to indemnify the electrode materials diffused on the surface.